A Critique of Trade Disputes Settlement Mechanism in Nigeria: 1968 to 2004 - Anyim, Francis Chukwudike (University of Lagos, 2009)
Full texts attached
Keywords: Conflict Manifestation; Labour market research; Marxist Perspective; Process of Collective Bargaining; Strike and its effect

The relevance of prior use in trade mark conflicts - Alberts, Riaan Willem (University of South Africa, 2009)
This thesis investigates the role of prior use in common and statutory trade mark law. In the United States a pertinent requirement is priority of use. In the United Kingdom and South Africa, a reputation must be present. In the United Kingdom a plaintiff is required to have goodwill in the country, but in the United States and South Africa it is not required. The conception of a mark does not qualify for protection. It is not required that a business must have actually entered the market. In the United States the general approach is that a plaintiff will not receive protection in a remote area, but regard must be had to zones of natural expansion. British and South African law is the same, and protection may be obtained in areas where there is no trading. Where a dual reputation exists, neither party will be able to act against the other. The mere fact that the user of a mark was aware of the use thereof by another person, does not exclude protection. A trade mark application can be opposed on the basis of another application, combined with use of a mark, or on the ground of prior use. In some instances the fact that a mark has been filed will influence the burden of proof. In general, a registration can be expunged on the same grounds as would constitute grounds of opposition. The concurrent use of a mark can form the basis for the registration of a mark. In the United States, the use must have taken place prior to the filing date of the other party, but in the United Kingdom and South Africa, prior to the own filing date. In the latter two countries, knowledge of a mark is not necessarily exclusionary. Prior use is generally accepted as a defence to an infringement action. It is, however, noted that in various countries, it is only use prior to the relevant date that will be protected, and there is not necessarily a right to extend the scope of use concerned.
Keywords: Common law trade marks; Competencia; Competition law; Intellectual property; Trade marks; Unfair competition; Unlawful competition

Selective legal aspects of bank demand guarantees - Kelly-Louw, Michelle (University of South Africa, 2009)
Bank demand guarantees have become an established part of international trade. Demand guarantees, standby letters of credit and commercial letters of credit are all treated as autonomous contracts whose operation will not be interfered with by courts on grounds immaterial to the guarantee or credit itself. The idea in the documentary credit transaction/demand guarantee transaction is that if the documents (where applicable) presented are in line with the terms of the credit/guarantee the bank has to pay, and if the documents do not correspond to the requirements, the bank must not pay. However, over the years a limited number of exceptions to the autonomy principle of demand guarantees and letters of credit have come to be acknowledged and accepted in practice. In certain circumstances, the autonomy of demand guarantees and letters of credit may be ignored by the bank and regard may be had to the terms and conditions of the underlying contract. The main exceptions concern fraud and illegality in the underlying contract. In this thesis a great deal of consideration has been given to fraud and illegality as possible grounds on which payment under demand guarantees and letters of credit have been attacked (and sometimes even prevented) in the English, American and South African courts. It will be shown that the prospect of success depends on the law applicable to the demand guarantee and letter of credit, and the approach a court in a specific jurisdiction takes. At present, South Africa has limited literature on demand guarantees, and the case law regarding the grounds upon which payment under a demand guarantee might be prevented is scarce and often non-existent. In South Africa one finds guidance by looking at similar South African case law dealing with commercial and standby letters of credit and applying these similar principles to demand guarantees. The courts, furthermore, find guidance by looking at how other jurisdictions, in particular the English courts, deal with these issues. Therefore, how the South African courts currently deal/should be dealing/probably will be dealing with the unfair and fraudulent calling of demand guarantees/letters of credit is discussed in this thesis.
Keywords: Bank guarantee; Demand guarantee; Documentary credit; Fraud; Freezing injunction; Garantie bancaire; Letters of credit; Suretyship and guaranty

A critical analysis of problem areas in respect of assets of insolvent estates of individuals - Evans, Roger Graham (University of Pretoria, 2009)
The Law of Insolvency in South Africa is regulated by the provisions of the Insolvency Act 24 of 1936, with foundations in our common law, which has been influenced by different legal systems from Western Europe. But currently there is also other legislation affecting the insolvent debtor and the property in the insolvent estate. The courts too have had to formulate rules to govern aspects of insolvency law in South Africa. These variables created problem areas in insolvency law and in respect of the of the policies upon which the insolvency system hinges. The predominant policy in South African insolvency is the collection of the maximum assets of the debtor for the advantage of creditors in insolvent estates. This strict creditor orientated approach created further problem areas in respect of assets in the insolvent estates of individual debtors. If advantage to creditors cannot be shown in an application for the sequestration of a debtor’s estate, a court will refuse to grant that order. This strict policy overshadows policy concerns in respect of assets in insolvent estates, and regarding exemption law in respect of those assets. This has resulted in insolvency law reformers in South Africa missing the bigger picture, namely, that South Africa is a creditor driven developing society. It is conceivable that in the transformed South Africa, and in the present world economic chaos, there will be an escalation of sequestrations of the estates of individual debtors. Bearing this in mind, a reformed insolvency law system must become more debtor friendly. A change in the philosophy is needed in favour of an exemption policy for insolvent estates. Exemption policy must be based on the interest of the debtor and his dependants, his dignity, creditor and third party interests, social welfare, and human rights imperatives within the South African constitutional framework. Exemption policy must be linked to the policy of a “fresh start” for the debtor. The different policies in insolvency however create a conflict of interest among the different stakeholders, particularly regarding the assets in insolvent estates, thereby creating problem areas. In this thesis several problem areas are identified and critically analysed. The position of property included in, and excluded from, individuals’ insolvent estates is investigated from a brief historical perspective, and in a brief comparative survey of the insolvency systems of the United Kingdom and the United States of America. Acute problem areas are critically analysed in detail, and the constitutional impact on property in insolvent estates is considered in a separate chapter. The South African Law Reform Commission’s review of South African insolvency law is critically analysed in a chapter of this thesis, concluding that the Commission’s review is inadequate. This thesis concludes that there is a need to reform the insolvency system in South Africa and proposes a way forward in respect of property included in, and property excluded or exempt from insolvent estates. This thesis states the law to the end of October 2008.
Keywords: Advantage to creditors; Creditor; Debtor; Disposition of property

Labour law implications of the transfer of an undertaking - Smit, Nicola (University of Johannesburg, 2009)
This thesis provides a comprehensive analysis of the legal, social, and economic consequences of business transfers on employment contracts, focusing on South African law and its comparison with international standards. It critically evaluates the automatic transfer of employment contracts, the protection of employee rights, and the legal complexities surrounding insolvent undertakings.
Keywords: Labour law; Labour legislation; Transfer (Law)

Rethinking the world trade order: towards a better legal understanding of the role of regionalism in the multilateral trade regime - Abualethem Nsour, Mohammad Fahed (McGill University, 2009)
Regional Trade Agreements (RTAs) have proliferated at an unprecedented pace since the creation of the World Trade Organization (WTO). Although the WTO legally recognizes countries’ entitlement to form RTAs, neither the WTO nor parties to RTAs have an unequivocal understanding of the relationship between the WTO and RTAs. In other words, the legal controversies, the result of uncertainty regarding the application of the WTO/GATT laws, risk undermining the objectives of the multilateral trade system. This thesis tackles a phenomenon that is widely believed to be heavily economic and political. The thesis highlights the economic and political aspects of regionalism, but largely concentrates on the legal dimension of regionalism. The main argument of the thesis is that the first step to achieving harmony between multilateralism and regionalism is the identification of the legal uncertainties that regionalism produces when countries form RTAs without taking into account the substantive and procedural aspect of the applicable WTO/ GATT laws. The thesis calls for the creation of a legal instrument (i.e. agreement on RTAs) that combines all of the applicable law on RTAs, and simultaneously clarifies the legal language used therein. Likewise, the WTO should have a proactive role, not merely as a coordinator of RTAs, but as a watchdog for the multilateral system that has the power to prosecute violating RTAs. The author is aware that political concerns are top priorities for governments and policy makers when dealing with the regionalism problematic. Hence, legal solutions or proposals are not sufficient to create a better international trade system without the good will of the WTO Members who are, in fact, the players who are striving to craft more regional trade arrangements.
Keywords: GATT; International Trade; Regional Trade Agreements (RTAs); WTO

Harmonisation of procedural law in international commercial arbitration - Chang, Mann-Long (University of Stirling, 2009)
The principle of party autonomy is widely accepted in the practice of international commercial arbitration. However, it still encounters certain limitations in its applications, especially for the fact that the demands of natural justice and the public good cannot be neglected by the parties. The various states in the international system have and operate peculiar systems of mandatory rules and public policies, which tend to impart significantly on the arbitral procedure, thereby creating a situation of discordance of outcomes of arbitration in different countries. For this reason, this writer intends to examine ways by which the various procedural laws can actually be harmonised. This thesis shall therefore focus on the discordances and confusion that often arise in the interacion of the various laws that may be applicable to the arbitral process in International commercial arbitration, as well as ways of achieving a harmonisation of these laws.
Keywords: Arbitrage commercial international; Arbitragem; Arbitraje; Arbitration; International commercial arbitration

Libyan Attitudes towards Islamic Methods of Finance: An Empirical Analysis of Retail Consumers, Business Firms and Banks - Gait, Alsadek Hesain Abdelsalam (Griffith University, 2009)
Libya is a predominately Muslim country where Islamic finance has not yet been established. However, given the current extensive program of financial reform in Libya and the rapid growth and appeal of Islamic finance in comparable economies, there is growing pressure for a system of Islamic finance to be provided. There is then a pressing need for research into the prospects for Islamic finance from a consumer and provider perceptive to inform this debate and thereby meet the needs of policymakers, financial service providers and prospective users. Accordingly, this study of Libyan attitudes towards Islamic methods of finance, the first study attempted in the Libyan context and one of few studies globally, applies a model derived from the Theory of Reasoned Action to analyse attitudes towards Islamic finance. The particular focus is to understand how the Theory of Reasoned Action can be used for predicting and understanding attitudes towards the potential use of Islamic methods of finance by Libyan retail consumers, business firms and banks. Four main research questions are posed to address this objective. First, does awareness of Islamic methods of finance influence attitudes towards the use of Islamic finance? Second, do socioeconomic, demographic and other factors influence attitudes towards Islamic finance? Third, what are the principal motivating factors towards the potential use of Islamic finance? Finally, is religion the major influence on the likelihood of engaging in Islamic finance? Three surveys of 385 retail consumers, 296 business firms and 134 bank managers in Libya are conducted in 2007/08 to achieve this objective. Descriptive analysis and multivariate statistical analysis (including factor analysis, discriminant analysis and binary logistic regressions) are used to analyse the data. The principal findings are that awareness of Islamic methods of finance and socioeconomic, demographic and business characteristics are key determinants of the likelihood of the use of Islamic finance. Further, religion plays a key, though not the only, role in influencing these attitudes. The thesis findings are of key importance in informing future financial industry practice and financial policy formation in Libya.
Keywords: Finance; Financial policy; Financial reform; Islam; Islamic finance; Libya

Income splitting, settlements and avoidance: taxing the family on business profits - Loutzenhiser, Glen (Oxford University, 2009)
In a progressive income tax system with an individual tax unit, high-rate taxpayers have an incentive to split income with lower-rate family members to minimise the family’s total tax burden. This raises equity and neutrality concerns. Adopting a spousal tax unit limits the gains from income splitting, but the individual is the better choice on privacy, autonomy, equality, definitional, marriage neutrality and work incentive grounds. Once the individual is chosen as the income tax unit, the control model provides a strong policy basis for attributing both earned and unearned income to individuals. Income splitting, however, undermines this model as well as the individual tax unit. This thesis focuses on the UK’s approach to income-splitting in family businesses. The relevant UK income tax rules, particularly the settlements provisions, are inadequate for the task. Various possible reforms are examined. Incorporating a transfer pricing or ‘reasonableness’ test into the settlements provisions would strengthen these rules, but would make taxpayer compliance with an uncertain regime even more difficult. Another option is to expand the scope of employment tax by moving the borderline between employees and the self-employed or companies. Deeper structural reforms could be made to enhance the neutrality of taxation on different legal forms of economic activity. This would reduce the incentives to incorporate for tax savings, including from income splitting. Integration of income tax and NICs is one such option; a dual income tax is another. A TAAR or GAAR also could be pursued. Ultimately, some combination of these various reform options could provide a partial solution to this challenging issue.
Keywords: Family taxation; Husband and wife; Income splitting; Settlements; Taxation

A balancing act: a framework for participation of non-state actors in the World Trade Organization - Majlessi, Mohammad (McGill University, 2009)
This thesis focuses on the interaction of two categories of non-state actors, private sector corporate actors and non-governmental organizations, with states in the context of the World Trade Organization (WTO) through a lens of public international law. It builds on the premise that the notion of states as the only subjects of international law is not adequate for a modern system of global governance, as it does not reflect the realities of fast-paced globalization and increased co-operation in a world where the boundaries of the private and public are increasingly blurred. It does not necessarily provide solutions for participation of non-state actors in the WTO, but demonstrates that developments in international relations warrant more space for participation of non-state actors, and that the current system of the WTO fails to provide sufficient space for participation. The thesis argues that, for both historical and pragmatic reasons, developments in the areas of GATT and international trade law occurred outside their natural course, leading to the myth of a “self-contained” trade regime not part of public international law. The WTO, unlike its predecessor, enjoys a proper institutional framework and mandate; one can no longer use the excuse of institutional handicap for excluding it from the system of global governance. Liberalization of international trade has far-reaching consequences which are not limited to the trade arena and the WTO, its member states, and scholars of international trade law have to assume their role in the broader context of an international legal order. Non-state actors’ formal participation can contribute to striking a balance between different forces and interests at work in the area of trade liberalization and its interplay with other non-trade issues. After setting the framework for the study, the thesis outlines modes of participation of non-state actors in the creation and modification of WTO law as well as in its enfor
Keywords: Balancing act; International Trade; WTO; World Trade Organization

Status Ambiguity and Conflict in the Market - Tan, David (Emory University, 2009)
My main theoretical contention is that status hierarchies provide a source of guidance to firms for resolving disputes. A status hierarchy implies a system of deference rules among firms. When disputes arise, deference rules can provide a basis for shared expectations and protocols of conduct about how technical ambiguities should be resolved. In many contexts, technical merit is difficult to assess. However, deference rules can operate as social conventions to which firms default, helping to align potentially incompatible expectations. Within this general framework, my dissertation examines how competitors in the semiconductor industry manage uncertain and frequently overlapping patent rights. In practice, patent rights are highly imperfect legal instruments when it comes to demarcating each firm's contributions to innovation in the industry. Patent disputes arise because of the ambiguity this creates about how much of the collective market returns to innovation each firm is entitled to receive. Despite the prolific patenting and propensity for disputes, the industry has remarkably not ground to a halt from runaway litigation. Litigation events, while significant, are rare. I suggest that this degree of order is, at least partly, attributable to status processes. Status can operate as a stabilizing force in the market, helping to generate orderly competition in the face of disputes. To examine whether this is the case in the semiconductor industry, I theorize that disputes are less easily resolved when the parties involved face greater status ambiguity, i.e. are less clearly differentiated from one another in status. Under status ambiguity, deference rules lose the rule-like, universal quality that makes them persuasive in resolving disputes. This has two consequences. First, firms facing low status ambiguity are less likely to be involved in patent litigation than are firms facing high status ambiguity. Patent litigation events represent failures to resolve patent disputes out of court. Second, firms facing low status ambiguity increase their product line sizes more than do firms facing high status ambiguity. The threat of difficult-to-resolve patent disputes represents a cost that can deter firms from bringing products to market.
Keywords: Litigation; Patent; Semiconductor; Status

Recognition of various stakeholder interests in company management - Esser, Irene-Marié (University of South Africa, 2008)
Good corporate governance should be the cornerstone of all company management. Directors ought to know in whose interests the company should be managed. This thesis attempts to answer the following question: whose interests must be granted primacy in the management of a company? In chapter 1 it is stated that shareholders' interests are traditionally granted primacy in the management of a company. There has, however, been a shift in public opinion towards recognition of a wider variety of interests that should be considered than only those of the shareholders. These interests include, inter alia, environmental interests and those of the investors, employees and consumers. This thesis thus focuses on the primary stakeholders, namely individual shareholders, creditors, employees, consumers and suppliers. In chapter 2 a theoretical foundation is provided on the nature of a company. The different theories on the nature of a company, emphasising either shareholder primacy or stakeholder protection, are discussed. A combined new theory is proposed. It is suggested that the confusion relating to the meaning of "the company" needs to be eliminated. Chapters 3, 4 and 5 provide an international comparison of the company law in Botswana, Australia, New Zealand and the United Kingdom. The focus falls, firstly, on directors' duties, secondly, on the question in whose interests directors should manage a company and, thirdly, on the codification of their duties. In chapter 6 the South African position is evaluated. First, the possible stakeholders are identified and the protection currently afforded them is explained. The reports of the King Committee on Corporate Governance, the Policy Document on company law reform as well as the Companies Bill of 2007 are discussed. Draft clauses are recommended to be incorporated in new company legislation to provide directors with clarity on what is expected of them. It is the aim of this thesis to provide clarity on whose interests should receive primacy when directors manage a company. The outcome of this research should provide a clear indication to South African directors of what is expected of them and who the beneficiaries of their fiduciary duties are.
Keywords: Codes of best practice; Consumers; Corporate governance; Corporation law; Creditors; Directors' Duties; Shareholder value; Shareholders; Social responsibility of business; Stakeholders

Crossing the Wires: the Interface between Law and Accounting and the Discourse Theory Potential of Telecommunications Regulation - Carter, David Bernard (Victoria University of Wellington, 2008)
Regulating telecommunications is complex: international experience indicates that there is no 'successful' regulatory framework due to the balancing of industry and regulatory interests (Laffont & Tirole, 2000, p. 13). The New Zealand 'light-handed' regulatory experiment failed and the 1999 General Election presented an opportunity for change in telecommunications. The Labour-led Government in implementing a policy of 'responsible re-regulation' enacted the Telecommunications Act 2001, signalling the passage of "landmark telecommunications legislation ..." (Swain, 2001d). Within the Telecommunications Act 2001, 'cost' assumed a central regulatory role. It is this move to cost that this thesis considers in identifying, developing, and critiquing the interface of law and accounting. The thesis examines the increasing call for accounting information in law and regulation by interrogating the use, presentation, and reception of accounting to examine the interface between law and cost in the regulation of telecommunications. The Telecommunications Act 2001 incorporates total service long run incremental costing as the 'costing technique' for interconnection access and annual net costing for the Telecommunications Service Obligation. Through interrogating 'cost' as an accounting technology, in contrast to the economic and legal conception of cost as a simple, objective concept, the thesis illustrates the role of cost at methodological, technical, and political levels, and the challenges that this poses for telecommunications regulation. The thesis articulates the relevance of discourse theory to the interface of law and accounting. Consequently, the thesis investigates the formation and discursive enunciation of standpoints of political identities characterised by antagonism and uncertainty. This includes identifying attempts by interested parties, including industry actors, stakeholders, and the Government and its agents, to articulate 'new' discourses centred on nodal points around 'cost'. The rhetorical analysis examines how actors articulate the metaphorical element of 'cost' in agitating for particular costing methods to be included in the legislation. The empirical analysis examines the process of rhetorical condensation as arguments for and against the incorporation of total service long run incremental costing and net costing came to signify the complete failure of the light-handed regulation. Then, by examining the politics following the enactment of legislation, this condensation is unpacked. The analysis of the contestation over interpreting and implementing the regulation illustrates displacement of the 'common' signifier resulting in confusion and disappointment in relation to the aims of the new regulatory regime.

The development of performance requirements in international law and their effect on BITs and FTAs as well as on the agreeing parties - Bless, Christopher Josef Manfred (Universität Wien, 2008)
Performance requirements are part of a system of policy measures implemented by states to advance their economic, social and political objectives. A universally agreed upon definition of performance requirements is not available. Rather they are defined by the applicable legal norms and their assessment is dependent upon their effect on the parties of each individual case. The scope of legal protection these regulations provide must be measured separately for each norm within the scope of the specific legal framework. This dissertation has two objectives: First, the implementation and legal effect of performance requirements in international investment and trade law are investigated. Secondly, a legal test will be developed, that allows for an assessment of performance requirements. In a first step, the legal treatment of performance requirements will be analyzed from a theoretical perspective. Subsequently, the legal practices relating performance requirements and the relevant provisions in international investment and trade law will be identified. The developed legal test does not only do justice to the economic, social and political framework within which each performance requirement must be looked at but is also adaptable in a way that it can be applied to a variety of situations and legal traditions. It satisfies both the demands of legal certainty and clarity as well as facilitating the finding of justice on an individual basis. Understanding the advantages of foreign direct investment, the analysis performed aims promote the usage of performance requirements in a way that foreign direct investment will push the global economy forward.
Keywords: FIRA; Foreign direct investment; Free trade agreements; International Trade; International investment; Investment treaties; NAFTA; Performance requirements

Directors’ duties to creditors - Lombard, Sulette (University of Pretoria, 2007)
Creditors of the corporate business form are in a vulnerable position. Recognition of the plight of corporate creditors led to the implementation of various legal measures aimed at protecting their financial interest in the company. These measures proved disappointingly inadequate in many instances. As a result the judiciary in some jurisdictions felt compelled to develop existing legal principles pertaining to directors’ duties in such a way that they could be used to facilitate protection of corporate creditors’ interests. This development did not meet with universal approval. Those opposed to the extension of directors’ duties to protect creditors’ interests have three main arguments against it. The first is related to conceptual issues and policy concerns. The second argument is that existing remedies are more than adequate to protect creditors’ interests. A last argument against a directorial duty to creditors pertains to the practical implementation of this extended duty. It is argued that the existing legal framework with regard to directors’ duties is not suitable to provide protection for creditors’ interests. However, it was shown in this study that the extension of directors’ duties to protect creditors’ interests is indeed justifiable on a sound conceptual basis and that policy concerns regarding such an extension are either unfounded, or should be addressed in some other way. An analysis of existing protective measures and remedies often referred to by opponents of an extension of directors’ duties, namely statutory personal liability of directors, traditional insolvency remedies, and the piercing of the veil doctrine furthermore showed that these measures are inadequate. This leads to the conclusion that there is a definite need for an alternative remedy, such as the extension of directors’ duties to include creditors’ interests. The existing legal framework in respect of directors’ duties furthermore proved to be capable of being successfully adapted to include creditors’ interests. Central issues in this respect, as was indicated by an analysis of case law, are the point in time when the duty to creditors is triggered, the beneficiary of the duty, in other words who would have locus standi in case of a breach of the duty, and the type of protection afforded to creditors’ interests by way of fiduciary duties and the duty of care and skill. The existing legal framework also provides measures in terms of which honest and diligent directors may be relieved from liability, such as indemnification, relief granted by the courts and director liability insurance. These measures, if formulated correctly, may achieve and maintain the essential balance between accountability and entrepreneurial freedom. The legislature appears to have adopted a cautious approach to the issue of directors’ duties to creditors. It thus seems to be up to the judiciary to develop directors’ duties to creditors in a meaningful way. Pioneering in this respect has already been done in Australia, New Zealand, England, Canada and the United States of America. It is to be hoped that the South African judiciary will follow suit when the opportunity to do so arises.
Keywords: Beneficiary of directors’ duties; Company law; Company’s interests; Corporate law

Legal aspects of corporate governance in the republic of South Africa: towards a possible model for improved stakeholder relations within the corporation - Spisto, Michael Paolo (University of the Witwatersrand, 2007)
Traditionally, company law assumes that the directors’ role is to run the company for the benefit of its shareholders alone and to maximise profits for them. It can be argued, however, that this view is too narrow and outdated; that is, company directors should have regard to the rights and interests of a broader range of corporate stakeholders. Hence, the question is whether we should change our perception of the company or corporation from one run by directors dedicated exclusively to serving the interests of shareholders to that of a corporation whose main purpose is to bring benefit not only to its owners and creditors, but also to its employees, the community and the environment. Given that reforms of directors’ duties in light of the above considerations have found their way into legislation across the globe, this thesis examines how and to what extent legal rules and policies should develop in South Africa to place directors under a positive duty to take account of the interests of bodies other than shareholders. Current South African company law does not contain clear rules regarding corporate governance issues and the duties and liabilities of directors. These matters have been left to the common law and Codes of Corporate Practice. Thus, there is no extensive statutory scheme in South Africa, which covers the duties, obligations and accountability of directors. The focus in this thesis is on the rights and interests of employees and the premise that is defended is that it is valuable to corporations to provide employees with an institutionalised voice at board level. It is argued that there is global evidence that where employees participate in the decision-making processes of the company, performance is generally enhanced. This, in turn, directly impacts upon and improves economic productivity, generating a ‘win-win’ situation. The question of the duties of company directors and managers is attracting much attention in South Africa. With rapidly developing and changing labour legislation in South Africa, it is essential to consider the extent to which the country should reassess its traditional principles of company law and corporate governance policies in order to encourage participatory roles for employees in the workplace. It is argued that if South Africa is to improve corporate productivity levels with its re-entry into international markets, management and labour must find improved ways of dealing with one another. The main purpose of this thesis, therefore, is to propose and formulate a workable corporate governance model for South Africa – one that would be advantageous to all stakeholders, especially the employees. This is achieved by comparing and contrasting international models of corporate governance and by applying the best features of each to the unique South African corporate system of values, structures and traditions. It is suggested that the current unitary board structure operating in South Africa has become outdated and does not provide employees with rights enabling them to engage in the decision-making processes of the corporation with their employees at an adequate level. In its place, a two-tier board system of corporate governance is proposed. The economic success of a company will bring about social benefits to many stakeholder constituencies. This will not happen if the company is a financial failure. The issue of obliging directors to act primarily for the benefit of shareholders alone is questioned. Corporate governance reforms were undertaken in many parts of the world in the late 1980’s and early 1990’s. This reform process questioned whether the interests of the company should be managed for the shareholders alone or for the other corporate stakeholders as well. There are many views that strongly support the idea that corporate governance should be seen as a system by which corporations are to be governed for the benefits of all stakeholders, including shareholders, employees, creditors, suppliers and the community. In this way, companies should be run as communities in partnerships with all their stakeholders. Thus, this thesis proposes that the success of a company is inextricably intertwined with a consideration of the rights and interests of its employees and other stakeholders.
Keywords: Bond/Debenture Holders; Community; Companies; Corporate governance; Corporations; Creditors; Employees; Environment; Interests; Models; Rights; Shareholders; South Africa; Stakeholder Relations

Alternative means to regulate the employment relationship in the changing world of work - Vettori, Maria-Stella (University of Pretoria, 2006)
Advancing technology has caused rapid and dramatic changes in the world of work. Labour law systems grounded in the industrial era, with their emphasis on collective bargaining, are not suitable in today’s world of work. Throughout the world, the ‘atypical employee’ is replacing the standard or typical employee whose terms and conditions of employment were generally regulated by collective agreements. Atypical employee’s terms and conditions of employment generally are not regulated by collective agreements. World– wide trends in the decentralisation of collective bargaining, decollectivisation and individualisation of the employment relationship have contributed to a decline in trade union power and influence. Consequently the number of workers covered by collective agreements has decreased. Collective bargaining has been rendered less effective because of the changing the world of work. The South African labour law system places a huge emphasis on collective bargaining, particularly at industry level, for the protection of employee interests. Given these trends in the changing world of work, the appropriateness of this emphasis on industry or central level collective bargaining is questioned. The vacuum left by the inadequacy and inability of trade unions to protect employee interests in a comprehensive manner by means of collective bargaining, needs to be addressed. The following alternative means of protecting employee interests are considered: (i) The socialisation of the law of contract; (ii) the interpretation given to the constitutional right to fair labour practices; and (iii) the role of good corporate governance and corporate social responsibility. These alternative means of addressing legitimate employee interests could play a role in filling the vacuum created by trade union decline. The South African law of contract is capable of bridging the gap between law and justice by the application of the concepts of good faith and public policy, so that employment contracts may take cognisance of employee interests despite the imbalance of power between employer and employee. The protection of worker interests by means of the constitutional right to fair labour practices depends on the judge’s interpretation of what is fair. Implementation of good corporate governance codes can be influential in protecting and promoting employee interests.
Keywords: Atypical employee; CSR; Collective bargaining; Corporate Social Responsibility; Corporate governance; Decentralization; Decollectivisation; Fordism; Individualization

Search and seizure, production and preservation of electronic evidence - Nieman, Annamart (North-West University, 2006)
Criminals are becoming increasingly involved in computing activity and connectivity, but practitioners in the criminal justice field do not seem to be keeping pace with crime in a computing context. Being comfortable with the technology that underpins the Information Age is a non-negotiable skill for those who have to unravel and bring twenty-first century crimes to book. Chapter two of this study therefore sought to serve two purposes. The first aim was to acquaint the reader with the exceedingly complex technologies involved in computers and networks. The second aim was to clarify the technical context and terminology typical of the collection of electronic evidence. South Africa signed the Cybercrime Convention in November 2001. At present, the Cybercrime Convention is the only existing internationally accepted benchmark, inter alia, for the procedural powers aimed at the collection of electronic evidence. The main objective of this study was to consider whether the South African search and seizure, production and preservation devices need to be augmented and/or aligned so as to be on par with the devices proposed in the Cybercrime Convention. This objective was served in two ways. Firstly, an exposition of the requirements, scope, conditions and safeguards of the domestic and transborder search and seizure, production and preservation mechanisms proposed by the Cybercrime Convention was provided in chapter three of this study. Secondly, an exposition of the domestic and transborder international search and seizure, production and preservation devices available in the current South African legislative framework was given in chapter four of this study. A comparative analysis was done between the South African catalogue of criminal procedural search and seizure, production and preservation devices compared to those set out in the Cybercrime Convention. Where any alignment or augmentation of the South African devices was found to be necessary, this study identified these intervention areas. The findings and recommendations based on this comparative analysis were set out in chapter seven of this study. In considering any alignments and/or augmentations required in respect of the South African domestic search and seizure, production and preservation mechanisms, the application of the equivalent mechanisms directed at electronic evidence used in the United States of America and England were investigated in chapters five and six respectively. The lessons learned were also referred to in chapter seven of this study.

A comparative legal study of the dilution of registered trade marks in selected jurisdictions to further the development of the remedy in South African law - Van der Walt, Elizabeth Margaretha (Stellenbosch University, 2005)
Trade marks are among the most valuable commodities of the modern business world. Adequate protection for trade marks to prevent the misappropriation of their incredible marketing power is therefore important. The aim of this dissertation is to make recommendations regarding the further development of existing South African law regarding the protection of registered trade marks against dilution, particularly by the courts. Current statutory protection is examined and compared with trade-mark law in the United States and the European Union. Although the concept of dilution originated in Germany, most of its development took place in the United States, starting in 1927 with an article by Frank Schechter. Dilution occurs when the awareness that a specific mark signifies a single product from a single source changes to an unmistakable awareness that the same mark signifies various things from various sources. The primary theories as to how dilution occurs are blurring and tarnishment. Although the dilution concept is widely recognised, there is still a debate amongst legal scholars on whether trade marks deserve protection against dilution. The extent of protection that the law gives to trade marks largely depends on the socioeconomic functions that a trade mark is perceived to fulfil. The original source or origin function is protected by the traditional infringement provisions. The identification or distinguishing function, quality function and advertising function subsequently gained recognition. The advertising function is statutorily recognised in various jurisdictions, which prevents trade-mark dilution. Statutory recognition of dilution in the United States first occurred in State law from 1947 onwards. Protection is generally given to distinctive or strong trade marks where a similar mark is used on dissimilar goods in the absence of confusion in such a way that there is a likelihood that the reputation of the senior mark will be injured. The parameters of the concept were developed and refined mainly through case law. Federal protection against dilution was only introduced in 1995. The new Act, although widely welcomed, also brought some unpredictability and interpretation problems. The first statutory dilution protection for trade marks in Europe is found in the Uniform Benelux Trade Marks Act. In 1989 the European Union adopted the Trademark Directive, with the aim of harmonising the legal protection afforded to trade marks. Its "dilution" provisions were incorporated into the United Kingdom's Trade Marks Act of 1994. The sometimes conflicting interpretations of these provisions by the English courts and the Court of Justice of the European Communities are discussed. The South African Act shows a substantial degree of harmony with legislation in the United Kingdom and other European countries. Aspects of the wording of the dilution provisions are however open to interpretation by the courts. Until the end of 2003 there was only one major trade-mark dilution case decided by a South African court, namely SAR v Laugh It OjJPromotions, which is discussed in detail. The dissertation concludes with recommendations to aid South African courts in the future interpretation and application of the dilution provisions. Amendments to the legislation are also proposed to promote greater clarity.
Keywords: Brand name products; Comparative law; European Union countries; Intellectual property; South Africa; Trademarks; United States

The cultural industries as a regulatory challenge for international trade law : insights from the NAFTA, the WTO and the EU - Neuwirth, Rostam Josef (European University Institute, 2005)
In the universal history of mankind, the concepts “culture” and “trade” have long denominated two important trains of human aspirations and activities. Notwithstanding their great significance for human life in its entirety, they have been widely regarded as belonging to distinct spheres, which were deemed to be difficult, if not impossible, to reconcile. This perception was also widely reflected in the sphere of law, where their respective fields have been subject to separate regimes based on the logic of their mutual exclusivity and expressed in the concept of res extra commercium. By contrast, the concept of “cultural industries”, which was originally derived from the term Kulturindustrie coined by protagonists of the Frankfurt School introduced a new category of cultural goods and services, which began to strongly challenge the traditional legal separation of cultural from economic considerations. Their novelty as well as their more subtle conceptual implications led to the controversy over the treatment of the dual, i.e. both cultural and economic, nature of such goods and services, which surfaced first during the bilateral trade negotiations between Canada and the United States and soon afterwards during the multilateral Uruguay Round negotiations. In the latter, it was the controversy over the exception culturelle that almost derailed the successful establishment of the World Trade Organization (WTO). Since then the problem remains unsolved, and reinforced by the decision of the WTO Panel in the Canada Periodicals Case, the quest for an appropriate conceptual approach allowing for the correct legal answer to the conundrum of culture and trade continues up to this day. In this quest, the present thesis forms an attempt to cast some light on the culture and trade conundrum with a view to isolating options for an appropriate legal response of the multilateral trading system under the WTO. It follows the evolution of the concept of cultural industries, from its birth in the context of critical social theory across the field of political economy to its first appearance in the legal context with the 1988 Canada-United States Free Trade Agreement. After a short analysis of the cultural industries exemption in the North American context, its focus shifts to the GATT/WTO system of which the basic provisions are discussed in connection with the category of cultural goods and services known as the cultural industries. Their critical analysis yields the present imperfections inherent in the WTO system as a corollary of the fragmentation of the international legal order. Before some final conclusions are drawn, these imperfections are contrasted with the relevant experiences within the context of the process of European integration from the European Economic Community to the European Union.
Keywords: Cultural property; Foreign trade regulation; Property protection

Theories of the company, employees and takeover regulation - Johnston, Andrew (European University Institute, 2004)
Keywords: Consolidation of corporations; European Union countries; Labor laws and legislation; Merger of corporations; Social policy

Corporate governance: a practical and effective response to the challenges raised - Fridman, Josef J. (McGill University, 2004)
This thesis seeks to address corporate governance from both a practical as well as an academic perspective. It searches for solutions to self-interest and agency costs, problems that it is posited are innate to the anthropomorphism of the corporation and to the separation of management and ownership of widely held, publicly traded, corporations. Practically, this dissertation is anchored in experience, garnered from empirical research, based on in depth and general surveys, as well as detailed interviews. It examines the workings of corporations, including their boards of directors, of gatekeepers, of checks and balances and of shareholders and the relative importance and rationale for the roles that they play. Based on the academic and empirical efforts it is posited that self-interest and the funneling syndrome, (a process whereby information required for decision making is constrained and managed by those in control), almost always predetermines the outcome of the corporate formal decision making process involving the board of directors. This facilitates abuse. When it occurs and there appears to be no accountability, confidence essential to the capital markets, quite understandably, suffers. A hypothesis is advanced to explain the complexity of a potential failure of corporate governance through a relatively simple formula. It draws conclusions as to what is required to help address the challenges raised by the breakdown in effective corporate governance and to help instill greater investor confidence. A self-assessment mechanism to help quantify how effectively a corporation is dealing with corporate governance, both on an absolute basis (comparing itself year over year) and on a relative basis (compared to one's peers) is proffered. This tool of more effective corporate governance, seeks to identify the causes for breakdowns in corporate governance and to assist a board of directors in dealing more proactively with this challenge.
Keywords: Corporate governance

Self-employment and the personal scope of labour law : comparative lessons from France, Italy, Sweden, the United Kingdom and the United States - Engblom, Samuel (European University Institute, 2003)
The past two decades has seen a growing interest, from both policy makers and scholars, in the legal regulation of work performed by self-employed workers. Increases in non-agricultural selfemployment in industrialised countries, together with political and ideological shifts, have fuelled interest in self-employment as a means of increasing employment. The attractions of selfemployment are manifold. To firms, self-employment is part of a two-fold change in the way firms operate: the move towards more flexibility as to the size and composition of the workforce, marked by an increased use of atypical workers and the disintegration of firms by arranging production through outsourcing, subcontracting and franchising. To workers, self-employment offers the greater autonomy connected with being their own boss, a chance of higher returns, or, at least, opportunities of gainful employment in times of high unemployment. To governments, self-employment has been seen as a means of increasing the number of small businesses, supposedly beneficial to the creation of new employment. Encouraging and removing barriers to self-employment is, therefore, a priority for many governments.
Keywords: Labor laws and legislation

Essays on Bargaining with Outside Options - Adamuz Peña, Mercedes (Universitat Autònoma de Barcelona, 2002)
Los modelos de negociación con opciones exteriores normalmente suponen que los pagos de estas opciones son independientes de las acciones que los negociadores toman durante el proceso negociador. Sin embargo, en muchos contextos, la opción exterior depende de lo que las partes hagan durante la fase negociadora. Uno de estos contextos es el de aquellas negociaciones que se llevan a cabo en presencia de un árbitro. Esta tesis realiza algunas contribuciones a la teoría de la negociación con opciones exteriores, enfatizando aquellas situaciones donde las opciones exteriores aparecen por la intervención de árbitros. En el capítulo 2 analizo los efectos del arbitraje en las negociaciones cuando su uso es voluntario. Considero un modelo de negociación por concesiones donde las partes tienen la posibilidad de llamar a un árbitro con el consentimiento del oponente. Demuestro que la introducción del arbitraje distorsiona el resultado de la negociación. Esta distorsión depende de los costes relativos de implementar una partición mediante un proceso negociador versus un proceso arbitral. Si los costes del arbitraje son pequeños en relación a los costes de la negociación, entonces la partición negociada se aproxima a la propuesta por el árbitro, y en casos extremos el arbitraje es utilizado en equilibrio. Sin embargo, los jugadores no eligen siempre el método más eficiente de resolver su disputa: a veces negocian cuando es más eficiente acudir al arbitraje. En el capítulo 3 estudio los efectos de diferentes procedimientos arbitrales en el resultado de una negociación, en un modelo donde los jugadores realizan demandas no crecientes y el árbitro es llamado solo cuando las negociaciones se declaran rotas. Dos procedimientos arbitrales son analizados: el arbitraje convencional, donde el árbitro es libre de elegir su acuerdo y el arbitraje de oferta final, donde el árbitro está obligado a elegir una de las últimas ofertas de los jugadores. Demuestro que si los jugadores son suficientemente pacientes y el árbitro sigue un procedimiento de oferta final, en equilibrio, los jugadores negocian una partición pero toma algún tiempo llegar a ella. Sin embargo, si el árbitro sigue un procedimiento convencional, en equilibrio los jugadores utilizarán esta institución para resolver su disputa. Finalmente, en el capítulo 4 discuto el papel que juegan las opciones exteriores inciertas en las negociaciones cuando existe información incompleta acerca de su existencia. Examino una guerra de desgaste donde los jugadores disfrutan de información privada acerca de sus posibilidades de dejar la mesa de negociación para tomar una opción exterior. Hay dos tipos de jugadores: los tipos débiles, que no tienen opciones exteriores y prefieren conceder que salirse del juego, y los tipos fuertes que tienen opciones exteriores tales que prefieren salirse que conceder. El principal mensaje que surge del análisis de este juego es que la incertidumbre acerca de la posibilidad de que el oponente se vaya, mejora la eficiencia porque incrementa la probabilidad de concesión. Más precisamente, si la probabilidad de que el oponente sea fuerte es relativamente alta, la negociación acaba con una concesión segura. En el otro extremo, si la probabilidad de que el oponente sea débil es alta, los tipos fuertes dejarán en algún momento el juego con probabilidad igual a 1, dejando a los débiles jugando, desde ese momente en adelante el ineficiente equilibrio de la guerra de desgaste clásica. Incluso en este caso, la probabilidad de concesión a lo largo de la fase de incertidumbre del juego se incrementa.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Ciències Socials; Conventional arbitration; Final-offer arbitration; Negociación; Opciones exteriores

Law of money, value and payment - Eitelberg, Eduard (University of Durban-Westville, 2002)
Societies have, since time immemorial, traded real goods and services for expectations of goods and services in some future. These expectations have been associated with tangible and, lately, intangible property - which is generally called money. From the crude quantity theory of money, the purchasing power of a monetary unit is given as 1/ P = T/(Mv). P is the price of the traded goods and services T, M is the total money supply and its turnover rate is v. The total money supply M is dominated by bank credit. In the South African law (and elsewhere) the judicial recognition given to bank credit (1) as money seems to have happened as an unintended side-effect to accepting cheques as delivery vehicles in a cash transfer without any tangible money moving from the transferor to the transferee. In payment of money, the law of property and the law of contract overlap and become inseparable. Both the English and South African laws define payment as performance of a preceding duty. The Supreme Court of Appeal, in the Vereins- und Westbank case seems to have declared an abstract transfer of ownership of money to be payment even though no preceding duty to pay was found. The profit of a financial investment is called interest and is calculated from a simple or compound interest formula. Despite medieval legal, theological and ethical objections, neither is illegal in the South African positive law. The last remnant of the medieval protection of a guilty debtor (often the ruler) at the expense of an innocent creditor is the in duplum rule. This is particularly obnoxious during modern rampant inflation that was unknown and could not be predicted when only metallistic money was in use. The influence of the in duplum rule is being limited by recent restrictive judgments in South Africa and in Zimbabwe. In South Africa, the Government has a constitutional duty to ensure that its subjects are not deprived of property. Specifically, the Constitution prescribes in Section 224(1) that the South African Reserve Bank must 'protect the value of the currency'. It is shown that the recent Reserve Bank policies, unless urgently modified, are in conflict with the publicly promised inflation rate of no greater than 6%. The exchange rates depend fundamentally on the price levels of the traded or tradable goods and services in the respective economies. This leads to the concept of purchasing power parity, which is most accurately reflected in the relationship between interest rates in different states and their relative foreign exchange depreciation rates. It is submitted that the South African Exchange Control Regulations have outlived their usefulness (if ever they had any) and are unconstitutional - at least in so far as they interfere with the South African Reserve Bank's obligation to pursue its primary object 'independently and without fear'. In the main, the South African Courts have applied restrictive interpretation to the Exchange Control Regulations and they have justifiably ignored the public international law obligation of the Republic to recognise the Exchange Control Regulations of fellow IMF members extraterritorially. (1) To money related claims on banks - see the body of the thesis for the two-creditor-two-debtor legal aspects in the 'bank credit'.

Community competence to control mergers : the jurisdictional divide - Burnley, Richard (European University Institute, 2002)
Keywords: Antitrust law; European Union countries; Unfair Competition

Globalization and the limits of National merger control laws: gaps in global governance and the need for an international merger control regime - Wilson, Joseph (McGill University, 2002)
From an economic perspective, globalization is dismantling national barriers to entry and is transforming domestic markets into a global market. To meet the challenges posed by the integration of markets, corporations are joining forces with their former competitors to expand their presence in the global market. Rapid growth in transnational mergers to create global corporations is one of the key features of globalization. As multinational corporations are uniting, so should antitrust agencies that regulate them. Antitrust agencies around the world are realizing that the consumers whom they are mandated to protect are being adversely affected by decisions made beyond their national borders. By using the "effects" test, countries bring within their jurisdiction review of any merger or acquisition involving foreign companies with significant revenue or assets within their jurisdiction. The proliferation of merger control laws, in the absence of a mechanism to coordinate the transnational merger review, places an unnecessary burden on merging parties, and runs the risk of divergent outcomes, which at times cause friction among nation-states. Both to alleviate unnecessary burdens imposed on corporations and to reduce inefficiencies produced by the disparate review of a single transnational merger by several countries, this thesis proposes an International Merger Control Regime integrated into the WTO. The proposal focuses on ways to operationalize a "Lead Jurisdiction" model of oversight rather than on the creation of a new supranational decision-making agency. WTO dispute settlement and arbitration would be used to resolve conflicts arising out of the inability of a Lead Jurisdiction to arrive at an outcome satisfactory to other significantly affected jurisdictions.
Keywords: International merger control; Merger; Merger control

Procedural detachment in international commercial arbitration : the law applicable to arbitral procedure - Petrochilos, Georgios (University of Oxford, 2000)
This thesis seeks to ascertain the rules of private international law determining the procedural law of international commercial arbitral proceedings. In an Introduction, the author outlines the fundamental notions, introduces the topic and the major doctrines and issues, and sets out his methodology and structure of the work. The thesis examine first, as a preliminary issue, the considerations influencing the assumption of jurisdiction over arbitral proceedings. Chapter 1 discusses the various theories on the lex arbitri (the law supplying the general legal framework of an arbitration) as relevant to the procedural law, and concludes that they are deductive and therefore unable to satisfactorily to determine the applicable procedural law. Chapter 2 analyses major national laws as case-studies of the technique and scope of application of international arbitration law, and suggests a model of legislative and court jurisdiction based on the legal concept of 'seat of the arbitration' and on considerations based on the most appropriate court to control an arbitration. Chapter 3 discusses the obligations of the state of the seat under the European Convention on Human Rights and confirms the findings in Chapter 2. In a second part, the thesis elaborates on the title and extent of permissible municipal law interference. Chapter 4 tests the validity of the propositions derived from Chapters 2 and 3 against arbitral practice and concludes that seldom will arbitrators derogate from the law of the seat. Chapter 5 examines the particular case of arbitrations with states and similar entities. The third part discusses the relevance of compliance with the law of the seat at the stage of enforcement of an award. Chapter 6 deals with the technical issue of whether annulment at the place of making precludes enforcement in other fora. That chapter gives the opportunity to discuss models of separation of international jurisdiction and co-operation between different jurisdictions from a practical perspective. It thus serves as a convenient introduction to Chapter 7, which discusses the more abstract question of the nexus required between an arbitral award and the municipal law of the state of rendition in order for the award to enter, in limine, the scope of application of the international instruments in the field. The thesis ends with Conclusions in the form of model provisions for municipal law and arbitration rules.
Keywords: Arbitrage; Arbitragem; Arbitration; International commercial arbitration; Procédure arbitrale